Pro-poor irrigation management transfer? - International Water Management Institute (International Water Management Institute, 2003)
Driven largely by financial pressures, many governments are transferring full or partial management responsibility for irrigation systems from government agencies to farmers organized into Water User Associations (WUAs). In most cases, improving the situation of poor farmers has been a secondary aim of this reform. But there is increasing evidence that Irrigation Management Transfer (IMT) can actually negatively impact the situation of poor farmers?and, in extreme cases, can even cause the collapse of irrigation schemes. New research assessed two different IMT programs: The Gujarat Participatory Irrigation Management (PIM) program, one of the first IMT programs in India, and the Andhra Pradesh Farmers? Management of Irrigation Systems (APFMIS) program, which with its sweeping reforms has served as an example worldwide. This research suggests that even if the IMT process contains all the right ingredients on paper?such as strong voting rights for farmers, irrespective of farm size?poor farmers are less informed on the whole about their rights and so tend to lose out on many of the potential benefits of IMT. The study showed that in both Gujarat and Andhra Pradesh poor farmers tended to participate more in the repair and rehabilitation work, while the larger farmers were more involved in the decision-making process?dominating the meetings and committees (see fig.1). To make IMT more pro-poor, and to ensure the viability of WUAs, which depend heavily on the labor contribution of small farmers, policy makers should take steps to ensure that poor farmers participate equally in decision-making processes. These steps include raising awareness and access to information, and making the election of WUA committees (which favor the village elite) more competitive and transparent. Monitoring participation in WUA activities and decision making against a reliable, and easily available indicator of poverty?farm size?is a key in evaluating equity trends over time.